The measurement of internet availability and quality in the context of the discussion on digital divide - Jochen Lüdering (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2015)
My contribution is concerned with measures of Internet quality and availability used and usable in the analysis of the so called digital divide. The usage of the share of Internet users in the population - widely used in economic analysis - can easily be misleading in this debate, suggesting that the digital divide is narrowing. This appears to be an artifact of the data, as some industrialized countries are already close to a share of 100 % Internet users in the population, while the ratio of Internet users to total populations is still growing for developing countries. I argue that one should focus on the study of Internet quality provided in a demand and supply model of infrastructure. To this end, I introduce a new latency-based measure to judge the quality of Internet, based on a novel data set, and compare it to related measures. The results indicate that it may indeed be useful to measure Internet quality across countries. In particular the availability of the indicator for 247 countries and semiautonomous regions makes it an interesting tool for policy analysis. The possibility to examine the effects of different determinants on individual quantiles is particularly interesting. ICT investment appears to be strongly correlated with lower latency (better Internet quality) in the lower part of the distribution, while there appears to be little explained variation in the top of the latency distribution. In addition we find that population density is an important determinant of latency - an argument which is brought up in the theoretical discussion on ICT investment but - to my knowledge - not found empirically to date.
Keywords: 330; Digital Divide; Internet; Telecommunication infrastructure; Measurement; Bandwidth; Latency